Speech Acts on Memes: A pragmatic study of Graduation T-shirts of Graduands - Dan'Azumi, Abdu; Ibrahim Aliyu , Yahaya; Saidu Abdullahi , Kabir (Department of Communications, Universitas Islam Indonesia, 2025)
Memes are linguistic tools for communication. Their power in the domain of communication, general discussions and writings from mainstream news media to digital media attract attentions. That, understanding their pragmatic effect becomes necessary, especially in today's digital world. This paper offers a pragmatic study of memes on graduation T-shirt of graduads. It specifically framed to ascertain how speech acts a humorously realised through memes. Memes are communication tools common at all levels in society; it is a powerful means of communication by civilisations. It communicates messages of valuable quality, which calls for pragmatic interventions to make explicit certain shrouded issues. The paper formulates two objectives: discuss the pragmatic power of memes in communicating messages, and identity the kind of speech acts memes contained. Guided the paper is Perlocutionary Acts, the third act of John Austin's (1962) Speech Acts Theory. The paper, however, is descriptive in nature, and analysed memes. The data were sourced from graduands' T-shirts of the Federal University Dutsin-Ma, Katsina State, Nigeria. The findings reveal that the studied memes perform different speech acts like persuading, enlightening, inspiring, warning and convincing.